The RESET tephra database and associated analytical tools - Bronk Ramsey, C; Housley, R; Lane, C; Smith, V; Pollard, A (Elsevier, 2015)
An open-access database has been set up to support the research project study- ing the ‘Response of Humans to Abrupt Environmental Transitions’ (RESET). The main methodology underlying this project was to use tephra layers to tie together and synchronise the chronologies of stratigraphic records at archaeological and envi- ronmental sites. The database has information on occurrences, and chemical compo- sitions, of glass shards from tephra and cryptotephra deposits found across Europe. The data includes both information from the RESET project itself and from the published literature. With over 12,000 major element analyses and over 3000 trace element analyses on glass shards, relevant to 80 late Quaternary eruptions, the RESET project has generated an important archive of data. When added to the published information, the database described here has a total of more than 22,000 major element analyses and nearly 4000 trace element analyses on glass from over 240 eruptions. In addition to the database and its associated data, new methods of data analysis for assessing correlations have been developed as part of the project. In particular an approach using multi-dimensional kernel density estimates to evaluate the likelihood of tephra compositions matching is described here and tested on data generated as part of the RESET project.